2018
DOI: 10.1111/pedi.12722
|View full text |Cite
|
Sign up to set email alerts
|

A brief campaign to prevent diabetic ketoacidosis in children newly diagnosed with type 1 diabetes mellitus: The NO-DKA Study

Abstract: A non-targeted campaign to raise awareness of diabetes symptoms in youth led only a few caregivers to seek timely medical attention. Overall, this once-yearly untargeted campaign to raise awareness of diabetes symptoms in youth had limited impact. More effective strategies are required, possibly involving sustained targeted education of medical practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…More recently, similar results were obtained by an information campaign in France . Nevertheless, a very recent once‐yearly untargeted campaign to raise awareness of diabetes symptoms in youth had limited impact . The efficiency and cost effectiveness of strategies to reduce the incidence of DKA at T1D onset are important issues for future interventions.…”
Section: Discussionsupporting
confidence: 53%
“…More recently, similar results were obtained by an information campaign in France . Nevertheless, a very recent once‐yearly untargeted campaign to raise awareness of diabetes symptoms in youth had limited impact . The efficiency and cost effectiveness of strategies to reduce the incidence of DKA at T1D onset are important issues for future interventions.…”
Section: Discussionsupporting
confidence: 53%
“…Our study did not collect information on local awareness campaigns but showed an increasing trend in the prevalence of DKA at diagnosis of type 1 diabetes over the 11 year period, suggesting that if prevention campaigns had been carried out locally, the expected effect was not achieved. Effective prevention campaigns should be targeted to reach a high percentage of the general population and healthcare professionals, should be repeated and prolonged over time, and should monitor all factors influencing the occurrence of DKA [ 15 ]. Preschool screening for islet autoantibodies in the general population might be useful to prevent DKA at diagnosis, as shown in a public health screening programme among children aged 2–5 years in Bavaria, Germany, in which the prevalence of DKA at diagnosis was less than 5% [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a cost-benefit analysis of a screening programme in the general population showed that costs far outweighed the economic benefits [13]. The impact of individual knowledge and community-based information and education campaigns in reducing DKA at type 1 diabetes onset has been disappointing [14][15][16]. These studies have suggested that knowledge of the symptoms of diabetes does not necessarily appear to translate to an earlier diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Literature suggests that increased awareness of T1D results in earlier diagnosis and treatment, can lead to DKA rate decrease [8,[33][34][35]. However, awareness publicity campaigns directed to type 1 diabetes have not shown consistent results [24,33,34,[36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%